Creative Construction Conference 2018 - Proceedings 2018
DOI: 10.3311/ccc2018-046
|View full text |Cite
|
Sign up to set email alerts
|

Challenges faced by stakeholders in the road construction projects in the Gauteng province of South Africa

Abstract: This study adopted a quantitative approach as the purpose was to investigate the challenges faced by stakeholders in the road construction projects in the Gauteng province of South Africa. This study adopted quantitative research and a well-structured questionnaire was distributed to different construction companies in Gauteng Province, which were registered with various approved councils construction professionals and contractors such as civil engineers, project managers, directors, quantity surveyors, constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Leung and Olomolaiye (2010) indicated that in the construction industry stakeholders could be a client, consultant, contractor, community leaders or a supplier. Studies such as (Leung and Olomolaiye, 2010;Mashwama et al, 2018) asserted that stakeholders within the construction industry could be categorised as internal, external, primary or secondary. Mashwama et al (2018) classified community and political leaders as external stakeholders within the South African construction industry.…”
Section: Review Of the Construction Industry And Construction 40 21 Construction Industry In South Africamentioning
confidence: 99%
See 1 more Smart Citation
“…Leung and Olomolaiye (2010) indicated that in the construction industry stakeholders could be a client, consultant, contractor, community leaders or a supplier. Studies such as (Leung and Olomolaiye, 2010;Mashwama et al, 2018) asserted that stakeholders within the construction industry could be categorised as internal, external, primary or secondary. Mashwama et al (2018) classified community and political leaders as external stakeholders within the South African construction industry.…”
Section: Review Of the Construction Industry And Construction 40 21 Construction Industry In South Africamentioning
confidence: 99%
“…Studies such as (Leung and Olomolaiye, 2010;Mashwama et al, 2018) asserted that stakeholders within the construction industry could be categorised as internal, external, primary or secondary. Mashwama et al (2018) classified community and political leaders as external stakeholders within the South African construction industry. Their low technical capability coupled with poor understanding of the dynamism of the construction industry were the basis for classifying them as external stakeholders.…”
Section: Review Of the Construction Industry And Construction 40 21 Construction Industry In South Africamentioning
confidence: 99%
“…Road infrastructure is a fundamental component of economic growth and development worldwide, facilitating the movement of goods, services, and people, and fostering trade and regional integration. Its significance extends to accelerating commercial and residential sector growth, providing individuals access to marketplaces, government services, and the broader world (Mashwama, Mushatu & Aigbavboa, 2018). Notably, road projects in developing countries have demonstrated considerable improvements in performance, with average cost overruns decreasing from 35% in the 1990s to 18% in the 2010s, as evidenced by data from over 600 projects across 97 countries (World Bank, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…According to Mukuka, Aigbavboa, and Thwala (2015), the construction industry in South Africa is plagued with challenges of projects schedule overruns. The following challenges in the South African construction industry are identified by Mashwama, Mushatu, and Aigbavboa (2018): inadequate planning, resources, delivery of material, plant, and equipment, shortage of skilled workers, lack of equipment, and lack of materials, project duration/period, and cost overruns. These challenges have the potential to lead to project failure and some of them can be mitigated by having capable leadership.…”
Section: Introductionmentioning
confidence: 99%